2000
DOI: 10.1088/0741-3335/42/12/102
|View full text |Cite
|
Sign up to set email alerts
|

Complete stabilization of a tearing mode in steady state high-βpH-mode discharges by the first harmonic electron cyclotron heating/current drive on JT-60U

Abstract: A tearing mode with m = 3 and n = 2, destabilized in the steady state high-β p H-mode discharges with edge localized mode (ELM), was completely stabilized by local heating and current drive using the 110 GHz first harmonic O-mode electron cyclotron (EC) wave. Here, m and n are poloidal and toroidal mode numbers, respectively. The optimum EC wave injection angle was determined by identifying the mode location from an electron temperature perturbation profile and a safety factor profile. The optimum injection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
127
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(132 citation statements)
references
References 14 publications
5
127
0
Order By: Relevance
“…An advanced plasma control system allows integrated control of these elements. Neoclassical tearing modes ͑NTMs͒ are avoided through current profile control, although active feedback stabilization using localized ECCD [10][11][12][13] has also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…An advanced plasma control system allows integrated control of these elements. Neoclassical tearing modes ͑NTMs͒ are avoided through current profile control, although active feedback stabilization using localized ECCD [10][11][12][13] has also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we find that an adjacent resonant mode previously expected to compete with and adversely affect the principal operating mode does not in fact jeopardize but rather helps this mode as a result of nonlinear effects. The result improves the outlook for using these devices for heating and instability control in future experimental fusion reactors, such as ITER [14][15][16][17][18][19] .…”
mentioning
confidence: 85%
“…By the time of the previous review [5], the suppression of (m=3,n=2) NTMs had been demonstrated in several tokamaks [24], [25], [26] and [27] and first experiments on partial (2,1) suppression had been carried out. Also, first attempts at feedback control of the deposition had been made.…”
Section: Application Of Ecrh and Eccd For Optimization Of Plasma Stabmentioning
confidence: 99%